The Use of Newer High Translucency Zirconia in Aesthetic Zone - Zishan Dangra; Mahesh Gandhewar (Hindawi Limited, 2014)
Loss of anterior tooth causes aesthetic and functional disharmony. Although no restorative material can approach the appearance of intact tooth enamel, glass ceramic, at the increased risk of brittle fracture, can mimic original tooth color better than the other restorative options. The newest zirconia material comes with unparalleled individualization in aesthetics and optimal physical properties. One of the basic principles of tooth preparation is conservation of tooth structure. This clinical report describes the replacement of maxillary and mandibular incisor with latest generation zirconia adhesive fixed partial denture. The authors have achieved unmatched aesthetics with newer high translucency zirconia.